Perspectives of the key stakeholders of the KickStart for Kids school breakfast program. (May 2020) - Watson, Michelle; Velardo, Stefania; Drummond, Murray
Highlights: The founder, volunteers and donors were considered a key strength to the program. Continues to grow however this places increasing demands for additional resources. The program has several benefits but also some challenges to ongoing delivery. Concerns about dual roles of the founder and ability to engage continued support. At the school level, a lack of personnel affected the running of the program. Abstract: Aim: To explore the perceptions and experiences of key stakeholders involved in the implementation and delivery of the KickStart for Kids school breakfast program. Background: Food insecurity is where individuals or households do not have enough food to meet dietary needs. In Australia, depending on the measurement tool used, the prevalence of food insecurity varies from 4% to 36% of the population. In comparison to other OECD countries, Australia is ranked in the bottom third for the level of childhood food insecurity. In response to an identified need, the KickStart for Kids school breakfast program was implemented in 2009 to provide food to disadvantaged youth. Currently the program provides approximately 50, 000 breakfasts daily in 350 South Australian schools. Methods: Eleven key stakeholders representing program volunteers, board members and donors were recruited for this qualitative case study using a purposeful sampling strategy. Program volunteers were recruited from primary schools in socio-economically deprived areas in the north, south and west of Adelaide, South Australia. Data were collected through focus group and one-on-one interviews. Data were transcribed verbatim and thematically analysed. Results: Data analysis generated three key themes related to the perceived program benefits to children, and perceived strengths and challenges to the program. Overall, the key stakeholders identified several benefits to the children and strengths of the program. However, there were significant challenges that may impact on the program's ongoing sustainability and delivery of school breakfasts. Conclusions: This qualitative study provides novel and valuable information on the perceptions and experiences of key stakeholders who are involved in the implementation and delivery of an Australian school breakfast program. Additional work could measure the program's impact on children's health and development outcomes. Further research could also be undertaken to add the voices of the school community, as well as the parents and children who participate.